TECHNOLOGICAL INNOVATION IN MODERN AGRICULTURE: ITS IMPACT ON PRODUCTIVITY AND SUSTAINABILITY - Suslinawati; Sapto Wibowo; Redi Yana Kapisa (Multidiciplinary Output Research For Actual and International Issue (MORFAI), 2025)
Technological innovation has become one of the main pillars in the development of modern agriculture. The use of tools such as drones, soil sensors, and automatic irrigation systems allows farmers to increase productivity through more efficient and measurable land management. In addition, this advanced technology also plays an important role in promoting environmental sustainability through environmentally friendly practices, such as more efficient water management and precision fertilisation. This article explores the positive impacts of implementing these technologies in increasing crop yields while minimising negative impacts on nature. With more equitable access to technology, especially for smallholder farmers, these innovations have great potential to ensure global food security while maintaining a balance between social, economic, and ecological aspects.